Chitosan active films containing agro-industrial residue extracts for shelf life extension of chicken restructured product - Serrano-León J.S. (2018)
Juan S. Serrano-León thanks the “Secretaría Nacional de Educación Superior, Ciencia, Tecnología e Innovación” (SENESCYT), Ecuador, for the scholarship and financial support and Erick Saldaña thanks the Cienciactiva from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica” (CONCYTEC), Peru (104-2016-FONDECYT), for the PhD scholarship.